ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, DANA PIHAK KETIGA, FINANCING TO DEPOSIT RATIO DAN NON-PERFORMING FINANCING TERHADAP RETURN ON ASSET BANK UMUM SYARIAH PERIODE 2014 - 2017 - Dimas Sauqi Mubarok; Alvien Nur Amalia (Ibs Press, 2023)
The purpose of this research is to examine and analyze relation between independent variable Capital Adequacy Ratio, Third Party Funds, Financing to Deposit Ratio, and Non-Performing Financing to Return On Asset Sharia Commercial Bank. Sampling determined by using purposive sampling method and the observation sampling is eleven Sharia Commercial Bank. Data obtained as secondary data on quarter financial report for Sharia Commercial Bank, start from quarter I for year 2014 to quarter IV year 2017. The analysis tools on this research is using multiple linear regression analysis, the hypothesis is based on prior research with similar topic and another supporting theory. The results from this research shows that Capital Adequacy Ratio have Positive significant effect on Return On Asset Sharia Commercial Bank, Third Party Funds and Non Performing Financing have negative significant on Return On Asset, meanwhile Financing to Deposit Ratio doesn't effect Return On Asset.